Relationship of Mathematical Disposition with Student Problem Solving Construction Using Realistic Mathematics Education (RME) Model - Khoirin Nida Fitria; Zaenuri Mastur; Amin Suyitno (AlphaMath : Journal of Mathematics Education, 2022)
The construction of problem solving is important in the learning process of mathematics. The success of students in solving problems can also be supported by psychological aspects related to student attitudes in the learning process, such as interest and curiosity, self-confidence, open-mindedness, and others, all of which include into a mathematical disposition. Teachers should know the ability of students' mathematical dispositions to help teachers provide the right treatment for problems in constructing problem solving by applying the RME model. The research method used is a concurrent embedded strategy mix method. This research was conducted at SMP 3 Bae Kudus. The subjects of this research were students of class VIII SMP 3 Bae Kudus. The instrument used in this research is a mathematical disposition questionnaire, problem solving test results, and interviews. The results showed that there was a positive correlation between students' mathematical disposition abilities and students' problem solving construction using the RME model. The higher the student's mathematical disposition, the higher the problem-solving construction ability, supported by the application of RME.